Management and safety of toxic substances workbook: introduction to a safe and healthy work environment - Syed Ismail, Sharifah Norkhadijah (Universiti Putra Malaysia Press, 2019)
This workbook is produced as a guide for learners about Management and Safety of Toxic Substances. Management of toxic substances in and outside workplace is essential for the promotion of health and safety of workers and community. The use of chemicals in industries, systematic management, appropriate control measures and information on the toxicology of these chemicals are the focus to prevent acute and chronic exposures as well as accidents while at work. This workbook emphasize on the importance of planning for systematic toxic substances management at workplace and the use of laws and regulations in managing toxic substances. Adaptation to the guidelines and the Safety Data Sheet (SDS) in the management and use of toxic substances also important to reduce occupational safety and health risk.